2007
DOI: 10.1136/emj.2007.046789
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of workplace violence towards paramedics

Abstract: Background: International studies have shown that some 60% of paramedics have experienced physical violence in the workplace, and between 21-78% have experienced verbal abuse. To date, there is no Australian literature describing Australian paramedics' experience of workplace violence. Objective: To identify the percentage of paramedics who had experienced six different forms of workplace violence. Methods: A questionnaire was developed to explore paramedics' experience of workplace violence. Six forms of viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
130
7
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(158 citation statements)
references
References 11 publications
9
130
7
12
Order By: Relevance
“…[30][31][32] Our finding that verbal abuse was more commonly reported than physical abuse is consistent with previous studies. [9][10][11]13,15,17 The prevalence of verbal abuse found in our study (76%) is greater than that found by Farrell et al (63%). 13 Although a recent study found that verbal abuse was less damaging than physical abuse in terms of the effect it has on the quality of patient care, 12 the available evidence unequivocally demonstrates the negative impacts of verbal abuse and bullying in the workplace on both the quality of the delivery of health services and the health and wellbeing of victims.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…[30][31][32] Our finding that verbal abuse was more commonly reported than physical abuse is consistent with previous studies. [9][10][11]13,15,17 The prevalence of verbal abuse found in our study (76%) is greater than that found by Farrell et al (63%). 13 Although a recent study found that verbal abuse was less damaging than physical abuse in terms of the effect it has on the quality of patient care, 12 the available evidence unequivocally demonstrates the negative impacts of verbal abuse and bullying in the workplace on both the quality of the delivery of health services and the health and wellbeing of victims.…”
Section: Discussioncontrasting
confidence: 59%
“…[1][2][3][4] Unfortunately, however, workplace abuse directed at front line health professionals is a common problem in several countries, [5][6][7][8][9][10][11] including Australia. [12][13][14][15][16][17][18][19][20] A recent systematic review of studies of the prevalence of patient-initiated abuse perpetrated against Australian general practitioners found 12 month period prevalence ratios ranging from 48 to 64%. 15 Similarly, a large study of nurses who were practising in Tasmania found a 1 month period prevalence of 64%.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, it has been reported that violent and aggressive behavior towards healthcare providers widely occured (Stanley & Goddard, 2002). Similar to the results in Canada, a study revealed that paramedics who are an important part of emergency settings in Australia, commonly experienced WPV, predominantly in the form of verbal abuse.In this study, it was also reported that, besides WPV, significant number of paramedics complained about sexual harassement by work colleagues (Boyle, Koritsas, Coles et al, 2007). …”
Section: Literature Datasupporting
confidence: 51%
“…3 Among all healthcare workers in Australia, ambulance officers were found to be at the greatest risk of workplace violence. 4 Globally, violence has been found to be a cause of injuries among emergency medical services (EMS) personnel in multiple countries.…”
Section: Introductionmentioning
confidence: 99%